2001
DOI: 10.1021/jo001278c
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Uncatalyzed and BF3-Assisted Baeyer−Villiger Reactions

Abstract: The mechanisms for the uncatalyzed and boron trifluoride (BF3) assisted Baeyer-Villiger reactions between acetone and hydrogen peroxide have been investigated using high level ab initio [MP2 and CCSD(T)] and density functional theory (B3LYP) methods. Both steps in the uncatalyzed reaction are found to have very high transition state energies. It is clear that detectable amounts of the Crieege intermediate or the products cannot be formed without the aid of a catalyst. The main function of BF3 in both the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…The activation energy calculated as the energy difference between TS rea and CI is 42.9 kcal mol −1 , indicating that this is the rate‐determining step. This process is irreversible and yields a complex between ε‐caprolactone and a water molecule (P) that is 58.4 kcal mol −1 more stable than R. The geometries and energies obtained are similar to those previously reported for the reaction of acetone and hydrogen peroxide,5d, 6b and in agreement with the experimental observation that Baeyer–Villiger oxidation of ketones with H 2 O 2 needs catalytic activation to occur.…”
Section: Resultssupporting
confidence: 87%
“…The activation energy calculated as the energy difference between TS rea and CI is 42.9 kcal mol −1 , indicating that this is the rate‐determining step. This process is irreversible and yields a complex between ε‐caprolactone and a water molecule (P) that is 58.4 kcal mol −1 more stable than R. The geometries and energies obtained are similar to those previously reported for the reaction of acetone and hydrogen peroxide,5d, 6b and in agreement with the experimental observation that Baeyer–Villiger oxidation of ketones with H 2 O 2 needs catalytic activation to occur.…”
Section: Resultssupporting
confidence: 87%
“…[21,23] For the mechanism elucidation of the B-V oxidation with hydrogen peroxide, only a few computational studies have been published. [24][25][26][27] Carlqvist and co-workers studied the uncatalyzed and BF 3 -assisted B-V oxidation of acetone with hydrogen peroxide using high-level ab initio and DFT methods and found that both steps in the uncatalyzed reaction have very high activation barriers, which is in agreement with the experimental observation that B-V reactions of ketones with hydrogen peroxide does not occur to a significant extent without catalytic activation. [24] It was found that the Lewis acidic BF 3 facilitates both steps of the reaction and significantly lowers the activation barrier for the rate-determining step (from 49.0 to 17.0 kcal mol…”
Section: Introductionmentioning
confidence: 56%
“…[3,11,18] Due to the importance of the BV reaction as an extensively applied method in organic synthesis, a number of theoretical studies have been made to elucidate its mechanism. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] To the best of our knowledge, the complete reaction mechanism, (www.interscience.wiley.com) DOI 10.1002/poc.1500…”
Section: Introductionmentioning
confidence: 99%